PERANAN PEMERINTAH KECAMATAN DALAM PENYELENGGARAAN PEMBANGUNAN FISIK DI KECAMATAN TAMIANG HULU KABUPATEN ACEH TAMIANG - Muhammad Afdhalu Zikri; Yanhar Jamaluddin (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2022)
Developments that have been planned at the sub-district level by sub-district government officials often do not go as expected.  Therefore, what is the potential of the area if the implementing apparatus does not understand the integration of development, automatically the development goals of the sub-district will not be achieved as expected.  Several villages or sub-districts and headed by a Camat, have the main task of implementing regional techniques that have certain work areas and also have functions.  At this writing the research was conducted in Tamiang Hulu District, Aceh Tamiang Regency, about how the role of the sub-district government in the implementation of physical development.  The results of this study explain that the role of the sub-district in physical development in the Tamiang Hulu sub-district begins with the preparation of a program of development activities held at the village level, where each village carries out Musrenbang.  The results of the village development plan deliberation (Musrenbangdes) are submitted to the sub-district government, thus the role of the sub-district is as a facilitator in carrying out development starting from forming meetings and inviting community leaders to participate in the planning